STRATEGI PENGEMBANGAN OBJEK WISATA JEMBATAN AKAR SEBAGAI DAERAH TUJUAN WISATA DI KABUPATEN PESISIR SELATAN - Pramutia Nazyul, Beta; Syafril, Rizki (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the development strategy for the Root Bridge tourist attraction in Pesisir Selatan Regency based on Cooper's theory, which encompasses aspects of attraction, accessibility, amenities, and public facilities. The Root Bridge is unique as a natural bridge over a river, with the potential to be developed into additional attractions such as swimming, fishing, and whitewater rafting. However, its current management is still suboptimal. This study used a qualitative approach with descriptive methods through observation, interviews, and documentation. The results indicate that the tourist attraction is still limited to the natural bridge, accessibility is inadequate due to narrow roads and minimal signage, amenities such as gazebos and restrooms are still lacking, and public facilities such as an information center, souvenir shop, tour guides, and a security post are not yet available. Based on a SWOT analysis, the development strategy focuses on enhancing river-based attractions, improving access, providing amenities, and building public facilities. This strategy is expected to support the development of the Root Bridge as a sustainable tourist destination that benefits the surrounding community.